Entrepreneurship education and digital skills acquisition in selected federal tertiary institutions in Osun State, Nigeria - Zubair, Opeyemi Jumoke; Olawepo, Samson Olaide; Adegbenjo, Abimbola Olunike (CV. Literasi Indonesia, 2026)
This study examines the degree to which entrepreneurship education fosters digital skills among students in the context of ongoing graduate digital illiteracy despite required entrepreneurship courses across three federal tertiary institutions in Osun State, Nigeria. The goals are to evaluate students' inventiveness, digital literacy, and preparedness for online business, as well as to ascertain how exposure to entrepreneurship education and digital competency relate to one another. Using a descriptive mixed-methods methodology, 30 professors chosen by stratified and simple random sampling participated in semi-structured interviews, and 285 students completed questionnaires. Thematic analysis was used to look at qualitative data, while descriptive statistics, one-way ANOVA, and Pearson correlation were used to evaluate quantitative data. The results indicate that while entrepreneurship education is widely used and increases awareness of business opportunities, the curriculum is still mostly theoretical and covers little in the way of digital marketing, e-commerce, and data analytics, which results in students having only a moderate level of digital competency. Digital skills and entrepreneurial education were found to have a substantial positive association (r = 0.63, p < 0.05), although this relationship is limited by curriculum gaps, poor infrastructure, and insufficient lecturer training. In order to guarantee that entrepreneurship education more successfully supports digital empowerment and employability in Nigeria's technology-driven economy, the study suggests curriculum change, enhanced digital infrastructure, and focused capacity building for lecturers.